Self-determination of Indigenous education policies in Australia: the case of the Aboriginal people and Torres Strait Islander people - Rosnon, Mohd Roslan; Abu Talib, Mansor; Wan Abdul Rahman, Nik Alia Fahada (Universiti Putra Malaysia Press, 2019)
For centuries, education has been used as a tool of assimilation, and this has been the Indigenous experience in Australian education system. Nevertheless, for those who has successfully negotiated it, education provides the key to self-determination, active and equal participation in the society. Since 2007, United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) is relevant to the Australia's Indigenous people. It has provided several guidelines, such as self-determination, rights and equity, which should be given to them. The UNDRIP should be not just an acceptance of a symbolic gesture but a more active 'recognition of rights'. Therefore, this paper reviews the current and the past reports that reflect the shifts in government policy of Indigenous education in Australia during the important key period when government policy relating to the Indigenous people shifted between 1974 and 2014. Several themes are identified as outcomes from the document analysis including: assimilation; equity and equality; participation and self-determination; and rights and recognition. The findings suggest that the Australian government still lack in their efforts to recognize and acknowledge the equity, the rights, and the self-determination of the Aboriginal people and Torres Straits Islander as 'the first people' in the country. It can be concluded that, Australia is yet to achieve at a substantive level the implementation of the UNDRIP. As a suggestion, alteration to the current curriculum framework needs to be done to improve the rights and equity of education development and cultivation of relationships between schools and Indigenous communities to ensure a successful outcome in the Indigenous education policy. Besides that, government of Australia should take an important and positive step approach towards the recognition of Indigenous Education rights through the adoption of the UNDRIP in their practice and constitution to recognize Indigenous languages, cultures and Indigenous knowledge in the education system in line with mainstream society.